2021
DOI: 10.3390/adolescents1020011
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Alcohol Prevention in Adolescents: A Systematic Review

Abstract: Virtual Reality-simulations offer new opportunities for alcohol prevention in adolescents. As an innovative medium, Virtual Reality can be attractive for the target group, and avatar-based pathways allow tailoring prevention in a gender-specific manner. However, tailoring may reproduce gender stereotypes and be exclusive. Therefore, this systematic review aims to summaries existing evidence regarding Virtual Reality-simulations for alcohol prevention targeting adolescents and to examine how gender is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(113 reference statements)
0
6
0
1
Order By: Relevance
“…The above-described properties of VR can be applied to the field of alcohol prevention because VR enables risky situations to be experienced in a safe environment (14). Currently, only a few VR-based examples of alcohol prevention for adolescents can be found in the scientific literature (15). One example is the Australian alcohol-prevention program Blurred Minds, which was developed as an innovative VR simulation training program for training young people's skills in dealing with peer pressure regarding alcohol (16).…”
Section: Introductionmentioning
confidence: 99%
“…The above-described properties of VR can be applied to the field of alcohol prevention because VR enables risky situations to be experienced in a safe environment (14). Currently, only a few VR-based examples of alcohol prevention for adolescents can be found in the scientific literature (15). One example is the Australian alcohol-prevention program Blurred Minds, which was developed as an innovative VR simulation training program for training young people's skills in dealing with peer pressure regarding alcohol (16).…”
Section: Introductionmentioning
confidence: 99%
“…By developing and testing a virtual reality simulation to train alcohol refusal self-efficacy, we entered new grounds in prevention research [ 21 , 29 ]. Our study evaluated the efficacy of the VR FestLab game aimed at improving refusal self-efficacy of adolescents who face social pressures to drink.…”
Section: Discussionmentioning
confidence: 99%
“…Within the area of VR simulations targeting alcohol prevention for adolescents, a recent review [ 29 ] identified only two studies besides the present authors’ VR FestLab that met the inclusion criteria. An American project exposed adolescents to a VR party including simulated substance use and sexual risk-taking cues and found an increase in physiological arousal among users [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study found both, patients and individuals from the reference group to resort to substance use as a means of coping, which underlines the need for preventive and educational measures on a societal scale. Adapting these measures to the current situation, as could be achieved by an implementation of digital strategies, is of major relevance ( 97 , 98 ). Further, efforts to develop treatment schemes that allow maintaining patients under professional attendance in difficult circumstances appear crucial.…”
Section: Discussionmentioning
confidence: 99%